Public debt management in Serbia during transition, great recession and Covid-19 pandemic - Vladimir Andrić (Serbian Journal of Management)
This paper examines the nonlinear asymmetric behavior of the public debt/GDP ratio in Serbia in the first two decades of economic transition following the political and market reforms initiated at the beginning of the twenty-first century. Using quarterly data for the public debt/GDP ratio, a two-regime self-exciting threshold autoregressive threshold (SETAR) model of order one identifies a public debt/GDP ratio threshold of 66.2% above which fiscal policymakers in Serbia take corrective action in the form of increased fiscal prudence. The estimated public debt/GDP ratio threshold roughly corresponds to a 60% threshold from the Maastricht fiscal criteria and shows how fiscal policymakers in Serbia systematically ignore the 45% public debt/GDP limit set in the national fiscal rules. Such fiscal policy behavior could jeopardize the credibility of fiscal institutions in Serbia and have a negative impact on fiscal discipline and the likelihood of sovereign default.